Organizing Knowledge : Encyclopædic Activities in the Pre-Eighteenth Century Islamic World - Endress, Gerhard, (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
The contributions in this volume offer the first comprehensive effort to describe and analyse the collection, classification, presentation and methodology of information in the knowledge society of medieval Islam in the disciplines of religious and legal learning, as well as the rational sciences of Hellenistic origin - philosophy, mathematical and medical sciences.The volume begins with a general discussion of the concept of encyclopædia. Successive chapters explore the bases of authority in the institutions of religion and law; biographical literature and handbooks of law; compendia of scientific and philosophical learning based on Iranian and Greek sources; and the more specialised expositions of mathematics and philosophy. The special character of Muslim institutions, their teaching traditions and syllabi is also put into perspective. This is a reference work for the principal genres of 'enyclopædic' outlines and manuals - biography, legal handbooks, historiography of knowledge transmission, cosmography, and the philosophical sciences - and a major contribution to the literary and intellectual history.